Asuhan Keperawatan Keluarga Tn F Dengan Gangguan Sistem Pencernaan : Gastritis di Desa Kalibuntu RT 03 RW 02 Kecamatan Losari Kabupaten Brebes - Fahruriza Pandinata Absor; Esti Nur Janah; Siti Fatimah; Tati Karyawati (STIKES Columbia Asia Medan, 2024)
Knowledge is very important for the formation of a person's actions and can influence a person in making a decision. Lack of knowledge about gastritis can result in people not understanding how to prevent it. Knowledge is the result of curiosity or experience carried out when such a person makes sense of a specific object. Knowledge has an important role in supporting the guidance of a person's behavior. Knowledge can influence a person's attitudes and actions regarding understanding and awareness in efforts to prevent gastritis by changing lifestyle, especially in diet, gastritis can be prevented by consuming medication, but can also reduce the factors that cause gastritis which can reduce the possibility of recurrence (Leipu , Hinga, 2022).